2019
DOI: 10.1002/hed.25635
|View full text |Cite
|
Sign up to set email alerts
|

Durable intracranial and extracranial response to nivolumab with appearance of secondary resistance in a heavily pretreated patient with head and neck cancer

Abstract: Background Recently, nivolumab was approved in the second‐line setting of squamous cell cancer of the head and neck (SCCHN). The benefits of PD‐(L)1 inhibitors in PD‐L1(−) tumors are unclear, and no reports exist on the activity of these agents in brain metastases from SCCHN. Little is known regarding the mechanisms underlying acquired resistance to PD‐(L)1 inhibition. Methods A patient with PD‐L1(−) metastatic SCCHN progressing to cetuximab‐based chemotherapy received third‐line nivolumab. T cell infiltration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Accordingly, PD-L1-positive HNSCC tends to respond well to PD-1 blockade [19]. However, recent evidence has revealed that the PD-L1 expression on the tumor is not a prerequisite for the clinical activity of these drugs in patients with platinum- and cetuximab-refractory HNSCC [4, 5]. According to these trials, PD-1 blockade is effective in some patients with PD-L1-negative tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, PD-L1-positive HNSCC tends to respond well to PD-1 blockade [19]. However, recent evidence has revealed that the PD-L1 expression on the tumor is not a prerequisite for the clinical activity of these drugs in patients with platinum- and cetuximab-refractory HNSCC [4, 5]. According to these trials, PD-1 blockade is effective in some patients with PD-L1-negative tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICIs) have been clinically approved for the treatment of cancer, including head and neck squamous cell carcinoma (HNSCC). Although patients with a high percentage of tumor-programmed death ligand 1 (PD-L1) expression have a better prognosis with ICI treatment [3], PD-L1 expression is not a prerequisite to gain benefit from programmed death 1 (PD-1) blockade [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms can elicit the resistance of head and neck tumor cells to immunotherapy and it may be hypothesized that monotherapy is not able to overcome the various mechanisms of immune escape [9]. Cabezas-Camarero et al described an expected immune evolution of a tumor initially responding but then progressing to nivolumab, with the occurrence of a dense immune infiltrate that becomes exhausted, due to upregulation of genes related to T cell exhaustion and resistance to PD-1 blockade favoring tumor progression [10].…”
Section: Discussionmentioning
confidence: 99%